2012
DOI: 10.1074/jbc.m111.258236
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of CMTM8 Induces Epithelial-to-Mesenchymal Transition-like Changes via c-MET/Extracellular Signal-regulated Kinase (ERK) Signaling

Abstract: The acquisition of an invasive phenotype is a critical turning point for malignant tumor cells. CMTM8, a potential tumor suppressor, is frequently down-regulated in solid tumors, and its overexpression induces tumor cell apoptosis. Here, we identify a new role for CMTM8 in regulating tumor cell migration. Reducing CMTM8 expression in HepG2 hepatocellular carcinoma cells results in the acquisition of epithelial-to-mesenchymal transition (EMT) features, including a morphological change from organized epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 47 publications
(65 reference statements)
1
44
1
Order By: Relevance
“…Previous studies have shown that phosphorylation of ERK-1/2 by MEK was elevated in PTCs from patients with DN and associated with EMT. Zuo, et al reported that EGFR activation induced a change with an EMT-like phenotype in scc10A cells [24]. Based on the EMT PCR Array analysis, we found that EGFR expression was up-regulated after GLIPR-2 overexpression.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have shown that phosphorylation of ERK-1/2 by MEK was elevated in PTCs from patients with DN and associated with EMT. Zuo, et al reported that EGFR activation induced a change with an EMT-like phenotype in scc10A cells [24]. Based on the EMT PCR Array analysis, we found that EGFR expression was up-regulated after GLIPR-2 overexpression.…”
Section: Discussionmentioning
confidence: 50%
“…Together, these reports implicate Met as a potentially effective therapeutic target to reverse resistance to this important class of drugs in NSCLC. Moreover, the Met receptor promotes a complex biological program designated "invasion growth" that results from stimulation of cell motility, invasion and protection from apoptosis (Zhang et al, 2012;Luo et al, 2013). To better understand the up-stream pathways involved in NSCLC gefitinib resistance, we investigated the miRNA, miR130a, which can regulate Met expression.…”
Section: Discussionmentioning
confidence: 99%
“…CMTM7 could promote epidermal growth factor receptor (EGFR) internalization, and further suppress Akt signaling pathway [31]. CMTM8 functions as a negative regulator of HGF/c-MET signaling to ERK [13]. CMTM3 might regulate MMP2 expression through the ERK1⁄2 signaling pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses carried out on DNA methylation patterns show that this process can be used as a biomarker for early diagnosis as well as for classification, prognosis, and therapy of human cancers [6]. Previous studies have identified the methylation of the promoter regions of over 40 tumor suppressor genes in oral squamous cell carcinoma and precancerous lesions, such as CDKN2A, MGMT, DAPK1, RUNX3, and p14 ARF [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%